Investigating Inspiring English Lecturers in a Faith-Based Educational Institution: EFL Learners’ Perception - Iftanti, Erna (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
This article describes English as Foreign Language (EFL) learners’ perception on an inspiring English lecturer. This study was done through a survey to 230 EFL learners of State Islamic Institute of Tulungagung, a small district in East Java- Indonesia, in order to get underlying basis of making a decision on learning policies for the sake of creating inspiring English teachers who are influential toward the success of English teaching and learning process. The instrument- Strategy Inventory for Students’ Perception on Inspiring English Lecturers (SISPIEL)- was developed in accordance to reviewing some related research articles about an inspiring teacher. The study reveals that to be an inspiring English lecturer, one should posses three skills namely attitudinal skills which are divided into three areas i.e. intellectual, emotional and spiritual, in addition to teaching technique strategies and skills of changing students’ learning style. Finally, the results of this study offers pedagogical considerations which are mainly useful for those running teacher training education program and those who are concerned in English education as well as suggestions for future research